Prospects of Integration of the Ukrainian Economy into the European Economic Area - Maksym Zhytar; Oksana Lisnichuk (Journal of Vasyl Stefanyk Precarpathian National University, 2022)
The article examines the prospects for the integration of the Ukrainian economy into the European economic space. It has been established that Ukraine's accession to the EU would be beneficial not only for Ukraine, but also for the European Union itself. One obvious advantage is security: if Ukraine were not currently at war, Russian tanks would probably already be in Warsaw or Tallinn. In peacetime, there are many opportunities for cooperation. Obvious areas are food security and energy production; in addition, Ukraine has a lot of human capital and entrepreneurial talent, and it is quite developed in IT, mechanical engineering and other industries that require a high level of technical skills. Ukrainian culture is rich and original. However, not only Ukraine will change during the accession. The European Union itself will be reformed in response to new challenges. Existing agreements between Ukraine and the European Union have already contributed to significant trade flows. Accession will have greater implications for the free movement of capital and workers – investment inflows and migration outflows. These areas are likely to be the focus of negotiations. A certain accession agreement usually has transition periods, especially for full free movement of labor, and opt-out clauses. The essential difference will be that Ukraine will be granted the status of "member of the EU" and not associated or annexed status. The consequences of the Russian invasion of Ukraine and its request for membership in the European Union changed the role of international diplomacy. The European Union realized the need to strengthen its own security and solve internal problems - from the consequences of Brexit to solving the alleged violations of the rule of law by Hungary. The military incursions into Ukraine have become a catalyst for change across Europe, and this may be reflected in how the member states of the European Union and the European Commission deal with Ukraine's accession.